Simple electroanalytical method for determination of guanosine in biological sample - dos Santos, Daniela Pereira [UNESP]; Brunelli, Tamara Fernanda Totta [UNESP]; Bianchi, Alex Rodrigo [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (My University, 2010)
A poly glutamic acid film modified electrode exhibited a catalytic response toguanosine oxidation potential and higher peak current value. Linear concentration curve was obtained in the concentration interval of 1.0 a 10.0 μmol L-1 in 0.04 mol L-1 B-R buffer pH 2.0 with a detection limit of 0.198 μmol L-1. The electrode was used for the determination of guanosine in the potential of +1.1 V (vs. Ag/AgCl) using differential pulse voltammetry (DPV) at urine sample with good recovery. © 2010 by CEE.
Keywords: Electrooxidation; Guanosine; Modified electrode; Poly glutamic acid